2023
DOI: 10.3390/pr11041205
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Rheological Properties of Coal Gangue Slurry Based on Response Surface Methodology

Abstract: To handle the gangue well and control the settlement of the surface, as well as to reduce the risk of water bleeding, settlement and even blockage and pipe breaking of the gangue slurry in the process of conveying, the rheological characteristics of the slurry should be studied. The rheological properties of slurry with different concentrations prepared from gangue samples of the Ningtiaota coal mine were tested, and the correlation between the rheological characteristics of the coal gangue filling slurry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Sun et al 22 studied the effects of gangue mass fraction, particle gradation and standing time on the rheological properties of gangue filling slurry, and confirmed that the characteristics of coal gangue slurry belong to Bingham fluid. Jin et al 23 , 24 analyzed the particle size distribution of coal gangue-fly ash mixture under different mixing ratios, and studied the effects of gradation and concentration on the rheological parameters of coal gangue-fly ash slurry.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sun et al 22 studied the effects of gangue mass fraction, particle gradation and standing time on the rheological properties of gangue filling slurry, and confirmed that the characteristics of coal gangue slurry belong to Bingham fluid. Jin et al 23 , 24 analyzed the particle size distribution of coal gangue-fly ash mixture under different mixing ratios, and studied the effects of gradation and concentration on the rheological parameters of coal gangue-fly ash slurry.…”
Section: Introductionmentioning
confidence: 93%
“…The main components of the gangue slurry used in the test are gangue powder, fly ash, and water. The injection time is short, and the viscosity timeliness will not occur in a certain period of time 22 , 42 . The main viscosity change of gangue slurry is only related to the injected medium and the seepage channel.…”
Section: Selection and Ratio Of Basic Parameters Of Gangue Slurry Mat...mentioning
confidence: 99%
“…Before Figure 3 shows that the plastic viscosity of the gangue slurry becomes more significant with the increase in mass concentration. With the increase in the number of particles, the shear rate increases, and the gangue particles collide, resulting in a shear thickening phenomenon, and the viscosity of the slurry gradually increases [2,9,18]. At the same time, there is a concentration interval in which the viscosity growth rate is significant.…”
Section: Slurry Fluiditymentioning
confidence: 99%
“…The fluidity of gangue slurry directly affects its transportation performance [18,19]. If the prepared gangue slurry's viscosity is too high, resistance in pipeline transportation is apparent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation